2017
DOI: 10.1080/2162402x.2017.1283460
|View full text |Cite
|
Sign up to set email alerts
|

Antigen receptor-redirected T cells derived from hematopoietic precursor cells lack expression of the endogenous TCR/CD3 receptor and exhibit specific antitumor capacities

Abstract: Recent clinical studies indicate that adoptive T-cell therapy and especially chimeric antigen receptor (CAR) T-cell therapy is a very potent and potentially curative treatment for B-lineage hematologic malignancies. Currently, autologous peripheral blood T cells are used for adoptive T-cell therapy. Adoptive T cells derived from healthy allogeneic donors may have several advantages; however, the expected occurrence of graft versus host disease (GvHD) as a consequence of the diverse allogeneic T-cell receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…HTS of the generated amplicon products containing the CDR3γ or CDR3δ sequences was performed on an Illumina MiSeq platform using the V2 300 kit, with 151 bp at the 3′ end (read 2) and 151 bp at the 5′ end (read 1; at the GIGA Center, University of Liège, Belgium). HTS analysis of TRA and TRB loci was performed as previously described (Van Caeneghem et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…HTS of the generated amplicon products containing the CDR3γ or CDR3δ sequences was performed on an Illumina MiSeq platform using the V2 300 kit, with 151 bp at the 3′ end (read 2) and 151 bp at the 5′ end (read 1; at the GIGA Center, University of Liège, Belgium). HTS analysis of TRA and TRB loci was performed as previously described (Van Caeneghem et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of evidence suggests that the introduction of either a TCR or a CAR into human hematopoietic progenitor cells can prevent endogenous rearrangement of the TCR-α and TCR-β locus, thereby giving rise to monospecific T cells that express the transgenic antigen receptor only (12,33,34). We demonstrated that, as in the murine model, early signals mediated by a CAR that had been transduced into CD34 + hematopoietic human stem cells result in decreased expression of NOTCH1, which leads to a suppression or regular progenitor T cell development in favor of NK-like cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…UCB-derived lymphoid progenitor cells (termed proT2) being CD34 + CD7 + CD5 + have been identified as a potential equivalent of the in vitro-generated murine DN2 precursor T cell population (13,38). We and others have shown that UCB-derived lymphoid progenitors can be genetically engineered (12,14). Our data on TCR rearrangement and gene expression in both murine and human systems support earlier studies showing that human and murine lymphoid development are much more similar than originally reported (30) and encourage its further exploitation for clinical use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches to reduce GVHD potential in allogeneic products require additional genetic modifications, adding both complexity and cost. Such approaches include knocking out (or down) the endogenous TCR, targeting integration of CAR into the TCR locus, or using CD3 neg cells such as those derived from hematopoietic precursor cells . A potential issue with these approaches is that CD3ζ ‐containing CAR requires its dimerization and interaction with an endogenous TCR/CD3 complex for optimal function .…”
Section: Discussionmentioning
confidence: 99%